Standardization of Integrated State Border Post Development - Rachmawati Novaria; Rudy Handoko; Kodrat Kodrat; Andria Marchelia (Indonesian Association for Public Administration (IAPA), 2019)
Border areas both on land and at sea as a border of national sovereignty universally have a very important and strategic role, both for national interests and for relations between countries (international). However, the problem that is cross-border in nature is global, especially facing transnational crime that is far more dangerous than military threats. Therefore, solving the problem across borders is not enough to be handled by the Republic of Indonesia itself, but rather by countries in the world to combat transnational crime. A practical and simple step is the need for an agreement between countries at the border to agree to safeguard and maintain cross-border boundaries safely and orderly. Standardization of Integrated PLBN Development includes technical standardization of PLBN buildings and standardization of Integrated PLBN management. In this activity, work will be carried out on the preparation of Integrated PLBN management standardization, which is standardization of the more popular PLBN work mechanism with the term Standard Operating Procedure (SOP) or Fixed Procedure (Protap) to facilitate PLBN officers in understanding PLBN SOPs and at the same time as a base line for basic improvements Future PLBN SOPs.